Election 2013: Editorial Treatment of Major Political Parties by Daily Nawa-I-Waqt During the Time Period Between March 1, 2013 to May 9, 2013 - Madni, Abdul Rehman; Nawaz, Tariq; Hassan, Ali; Abdullah, Mudassar (Asian Journal of Empirical Research, 2014)
This research study was an effort to search out the editorial treatment of major political Parties (Pakistan Muslim League-N, Pakistan Tehreek-e-Insaf and Pakistan People’s Party) by Daily Nawa-i-Waqt during the time period between March 1, 2013 to May 9, 2013. Content analysis was used and all the editorials and editorial notes published on the editorial pages were taken as the Unit of Analysis. Keeping in mind the nature of the present study, researchers selected all the papers published during the study’s stipulated period for analysis. Overall, 70 newspapers were analyzed. Coding sheet is used to limit the number of categories. To control the problem of data collection scientifically and for data reduction, ten columns a coding sheet was created. The findings of the study indicate that Daily Nawa-i-Waqt published more favorable sentences for PML-N. Outcomes of the study also illustrate that Daily Nawa-i-Waqt published a huge amount of sentences in favor of PTI also. It also published unfavorable sentences for PTI. Results depict that Daily Nawa-i-Waqt published nothing in favor of PPP as comparison with PML-N and PTI. It portrays that Daily Nawa-i-Waqt published a huge amount of sentences against PPP.